Empirically Defining Treatment Response and Remission in Body Dysmorphic Disorder Using a Short Self-Report Instrument. Issue 4 (July 2021) - Flygare, Oskar; Chen, Long-Long; Fernández de la Cruz, Lorena; Rück, Christian; Andersson, Erik; Enander, Jesper; Mataix-Cols, David
Highlights: We evaluated the Appearance Anxiety Inventory (AAI) using signal detection analysis. A reduction ≥ 40% on the AAI was the optimal cutoff for treatment response. An AAI score ≤ 13 was the optimal cutoff for full or partial remission. The AAI can complement clinician assessments in treatment evaluation. Abstract: Determining response or remission status in body dysmorphic disorder (BDD) usually requires a lengthy interview with a trained clinician. This study sought to establish empirically derived cutoffs to define treatment response and remission in BDD using a brief self-report instrument, the Appearance Anxiety Inventory (AAI). Results from three clinical trials of BDD were pooled to create a sample of 123 individuals who had received cognitive-behavioral therapy for BDD, delivered via the Internet. The AAI was compared to gold-standard criteria for response and remission in BDD, based on the clinician-administered Yale–Brown Obsessive Compulsive Scale, modified for BDD (BDD-YBOCS), and evaluated using signal detection analysis. The results showed that a ≥ 40% reduction on the AAI best corresponded to treatment response, with a sensitivity of 0.71 and a specificity of 0.84. A score ≤ 13 at posttreatment was the optimal cutoff in determining full or partial remission from BDD, with a sensitivity of 0.75 and a specificity of 0.88. These findings provide benchmarks for using the AAI in BDD treatment evaluation when resource-intensive measures administered by clinicians are not feasible.